The Worship of Satan - Analytical and Descriptive Study - Aliya Al qarni (My University, 2012)
This research is about the worship of Satan (Devil), its ancient and modern roots and its recent association with Judaism and Freemasonry. It is noted that the image of Satan in Christianity resembles evil and corruption. On the other hand the Yezidi reverence for Satan does not mean that they are the recent intellectual origin and nodal roots of the worshippers of Satan, this is due to the difference of the two doctrines in principles, values and social role. The roots of Satanists contemporaries were said to Gnosticism and to the Knights of the Temple. The spiritual father of this group was (Aleiser Crowley) (1875- 1947 AD). His call was the basis from which the real founder of this group – the American Jew (Antoine Shieldsvi) born in 1930, has set out. Satan is the main God for the Satanists and the reason is that they think the Satan was oppressed. They believe that it is their duty to stand on his side. According to them the Devil is of the Angels not of the Jinn .They glorified him because they viewed him as the most courageous in the universe who stood in front of whom nobody could stand. The worshippers of Satan have devotional rituals and religious feasts which are directly related to the devil worship and getting closer to him. Magic, poetry and human sacrifices are some of these rituals.

هذا البحث يدور حول عبادة الشيطان وجذورها قديما وحديثا، وارتباط عبادة الشيطان حديثا باليهودية والماسونية، علما بأن صورة الشيطان في الديانة النصرانية صورة تمثل الشر والفساد، أما تقديس اليزيدية للشيطان لا يعني أنهم الأصل الفكري والجذور العقدية لعبّاد الشيطان حاليا لاختلاف كل من الطائفتين في المباديء، والقيم والدور الاجتماعي،أما جذور عبدة الشيطان المعاصرين فقيل الغنوصية، وقيل فرسان الهيكل، والأب الروحي لهذه النحلة (أليستر كرولي) (1875-1947م)، وكانت دعوته الأساس الذي انطلق منه المؤسس الحقيقي لهذه النحلة وهو يهودي أمريكي اسمه (أنطوان شيلدز لافي) المولود عام (1930م). الشيطان يمثل المعبود الرئيسي عند جماعة (عبدة الشيطان) وسبب ذلك أنه مظلوم بزعمهم، والواجب يقضي أن يقفوا إلى جانبه، والشيطان عندهم من الملائكة وليس من الجن، كما يعلنون تمجيدهم له لأنه – في نظرهم- أشجع من في الكون فقد وقف أمام من لا يستطيع أحد الوقوف أمامه. لعبّاد الشيطان طقوس تعبدية، وأعياد دينية ترتبط ارتباطا مباشرا بعبادة الشيطان والتقرب إليه، فالسحر والموسيقى والقرابين البشرية بعض طقوسهم التعبدية.
عبادة الشـيطان - دراسة وصفية تحليلية